The Role of Literature in the Formation and Development of Personal Qualities of a Doctor - I. A. Emelin; R. V. Shurupova (Сеченовский вестник, 2022)
The article discusses the importance of literature for training and becoming a doctor, determines the leading methodological and conceptual features of teaching literature in medical school and discusses the various situations, described in a literary work, in the classroom.